HARMONISASI PENGATURAN HUKUM SERTA IMPLIKASI TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN LINGKUNGAN PADA BUMN PTPN III PERSERO BERDASARKAN UU NO. 40 TAHUN 2007 DAN PERATURAN MENTERI BUMN NOMOR PER-09/MBU/07/2015 - VANDERSON HAMDANI (jurnal.unprimdn.ac.id, 2021)
Partnership and environmental development program constitutes the Corporate Social Responsibility (CSR) implemented by the BUMN plantation companies in Indonesia. The research used juridical empirical and descriptive analytic methods. It employed library research method and qualitative data analysis method. The result of the research shows that the will of legacy in the legal provisions about CSR in its objective is synchronized with or similar to the Decree of the State Minister of BUMN No KEP-09/MBU/07/2015 at BUMN because both of them are used to the greatest benefit of the people who lived in the vicinity of the company. The result of the research shows that the will of legacy in the legal provisions about CSR in its objective is synchronized with or similar to the Decree of the State Minister of BUMN No KEP-09/MBU/07/2015 at BUMN because both of them are used to the greatest benefit of the people who lived in the vicinity of the company.